Graphene oxide reinforced polymeric ionic liquid monolith solid‐phase microextraction sorbent for high‐performance liquid chromatography analysis of phenolic compounds in aqueous environmental samples. Issue 2 (24th November 2015) - Sun, Min; Bu, Yanan; Feng, Juanjuan; Luo, Chuannan
Abstract : A graphene oxide reinforced polymeric ionic liquids monolith was obtained by copolymerization of graphene oxide doped 1‐(3‐aminopropyl)‐3‐(4‐vinylbenzyl)imidazolium 4‐styrenesulfonate monomer and 1, 6‐di‐(3‐vinylimidazolium) hexane bihexafluorophosphate cross‐linking agent. Coupled to high‐performance liquid chromatography, the monolith was used as a solid‐phase microextraction sorbent to analyze several phenolic compounds in aqueous samples. Under the optimized extraction and desorption conditions, linear ranges were 5–400 μg/L for 3‐nitrophenol, 2‐nitrophenol, and 2, 5‐dichlorophenol and 2–400 μg/L for 4‐chlorophenol, 2‐methylphenol, and 2, 4, 6‐trichlorophenol ( R 2 = 0.9973–0.9988). The limits of detection were 0.5 μg/L for 3‐nitrophenol and 2‐nitrophenol and 0.2 μg/L for the rest of the analytes. The proposed method was used to determine target analytes in groundwater from an industrial park and river water. None of the analytes was detected. Relative recoveries were in the range of 75.5–113%.